Binge eating disorder – the status of knowledge - Banach, Joanna; Szymańska, Jolanta (Current Problems of Psychiatry, 2025)
Despite the fact that in the last 30 years binge eating disorder (BED) has gained quite a lot of attention within medical field, it is still a sort of perplexity and a challenge to clinicians. BED is characterized by binge eating episodes during which the control of the eating process is lost. After the episode we do not observe behavior compensatory to binge eating, which purpose is to dispose of the eaten food. BED is a serious disorder that can negatively influence physical health and psychosocial performance. It can be associated with overweight and obesity, affective and anxiety disorders. It also correlates with personality disorders. It is common in general population (at least 3%) and even more common within overweight population (7% to 12%). There is few theories that try to explain causes and risk factors of BED, but its’ etiology still remains elusive.